Precise orientation control of gimbals with parametric variations using model reference adaptive controller - Çakmak, Ömer; Altuğ, Erdinç (Wiley, 2024)
This study focuses on a model reference adaptive control method that ensures identical orientation outputs for different prototypes of a two-axis gimbal produced in mass production. In this method, unlike traditional MRAC structures, an MRAC structure is used in conjunction with state feedback control. First, the reasons for the need for an adaptation mechanism in gimbals and why Model Reference Adaptive Control (MRAC) alone won't be sufficient have been discussed. In the first section, various applications of MRAC have also been mentioned. Then, the mathematical foundation of the model reference adaptive controller used in this study is elaborately explained, followed by stability analyses. In the next step, an ideal reference model exhibiting desired behavior and a real system model with different dynamics are created in a simulation environment. This allows a comparison of the adaptation capabilities of only MRAC and MRAC+State Feedback controllers. Based on the information gathered in this section, the recommended approach in the article is tested on a real gimbal system, and the results are shared. The obtained results demonstrate that the MRAC+State Feedback control structure significantly reduces the error in the gimbal's orientation response compared to the reference model.
Keywords: model reference adaptive control; MRAC; adaptive control systems; gimbal modeling; feedback control systems; orientation control